Indicadores de qualidade do leite bovino orgânico em duas propriedades leiteiras certificadas do Estado de São Paulo - Siqueira, A.k [UNESP]; Salerno, T [UNESP]; Lara, G.h.b [UNESP]; Condas, L.a.z [UNESP]; Listoni, F.j.p [UNESP]; Paes, A.c [UNESP]; Da Silva, A.v [UNESP]; Leite, D. Da S; Ribeiro, M.g [UNESP] (Instituto Biológico, 2012)
This study evaluated the chemical composition, total bacterial count, the level of cellularity and presence of antimicrobial residues in milk from two small farms in organic production system in the state of São Paulo, Brazil, based in NI 062-MAPA. The milk of the Property I had the mean of CCS 7.13 x 10(5) cells/mL and the Property II had 3.27 x 10(5) cells/mL. The averages of CBT were, respectively, 7.80 x 10(5) cells/mL in the Property I and 6.15 x 10(5) cells/mL in Property II. The Property I presented as an average of 3.10% of fat, 3.26% of protein and 4.54% of lactose, while the Property II presented 3.44% of fat, 3.39% of protein and 4.50% of lactose in 12 months assessed. The presence of residues of antimicrobial drugs was detected in six samples (6.97%) of the Property I and 16 (9.24%) of Property II. The results obtained reveal failure in the percepts of organic production.

O presente estudo avaliou a composição química, a contagem bacteriana total, o nível de celularidade e presença de resíduos de antimicrobianos no leite de duas propriedades em sistema orgânico de produção do interior do Estado São Paulo com base na IN 062-MAPA. O leite da Propriedade I apresentou média de CCS de 7,13 x 10(5) céls/mL e o da Propriedade II 3,27 x 10(5) céls/mL. As médias das CBTs foram de 7,80 x 10(5) céls/mL na Propriedade I e de 6,15 x 10(5) céls/mL na Propriedade II. A propriedade I apresentou como média de gordura de 3,10%, de proteína 3,26% e 4,54% de lactose, enquanto a Propriedade II apresentou 3,44% de gordura, 3,39% de proteína e 4,50% de lactose, nos 12 meses avaliados. A presença de resíduos de antimicrobianos foi detectada em seis amostras (6,97%) da Propriedade I e em 16 (9,24%) da Propriedade II. Os resultados obtidos revelam falha nos preceitos da produção orgânica.
Quality indicators of organic bovine milk in two certified dairy herds in São Paulo state, Brazil
Keywords: Leite orgânico; qualidade do leite; mastite; resíduos de antimicrobianos; bovinos; Organic milk; milk quality; mastitis; antimicrobial residues; bovine